2010
DOI: 10.1111/j.1574-6941.2010.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

Most heat-tolerant rhizobia show high induction of major chaperone genes upon stress

Abstract: The aims of this study were to evaluate the temperature stress tolerance of chickpea rhizobia and to investigate whether tolerance is related to the species or the site of origin of the isolates. Additionally, the molecular bases of temperature stress tolerance in rhizobia were investigated, by comparing the expression of chaperone genes dnaKJ and groESL in thermotolerant and thermosensitive isolates. Tolerance to cold, heat and heat shock was evaluated for 53 mesorhizobia obtained from several provinces of Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…15 In Mesorhizobium spp., both dnaK and groESL genes were reported to be transcriptionally induced by a temperature upshift, especially in heat tolerant isolates. 16 In rhizobia, groESL operons are often CIRCE (controlling inverted repeat of chaperone expression) regulated, as already reported in Bradyrhizobium japonicum , S. meliloti and Rhizobium leguminosarum . 13,17,18 CIRCE is a highly conserved DNA sequence that serves as binding site of the repressor protein HrcA.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…15 In Mesorhizobium spp., both dnaK and groESL genes were reported to be transcriptionally induced by a temperature upshift, especially in heat tolerant isolates. 16 In rhizobia, groESL operons are often CIRCE (controlling inverted repeat of chaperone expression) regulated, as already reported in Bradyrhizobium japonicum , S. meliloti and Rhizobium leguminosarum . 13,17,18 CIRCE is a highly conserved DNA sequence that serves as binding site of the repressor protein HrcA.…”
Section: Introductionmentioning
confidence: 78%
“…Nevertheless, the real-time qRT–PCR results (Table 1) show that dnaK was induced by heat shock, agreeing with previous studies in Mesorhizobium . 16 Approximately, 2-fold induction of the dnaK gene was detected in S. meliloti cells exposed to 40°C for 30 min, 5 while no induction was reported for a shorter heat shock (42°C for 15 min). 27 In the microarray analysis, the changes in expression levels of the dnaK gene were considered not statistically significant due to discrepancies among replicates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a main role in de novo folding, DnaK has various other functions, including protein transport [45], and in the increased stability of RNA polymerase σ 32 factor (RpoH), an important component of the heat-shock response in several organisms [46-49]. …”
Section: Resultsmentioning
confidence: 99%
“…As it is known, phenotypes might differ from strain to strain within the same species (Sneath 2001). However, recent studies have shown that isolates from M. ciceri and M. mediterraneum are significantly more tolerant to temperature stress than isolates from other species (Alexandre and Oliveira 2011).…”
Section: Discussionmentioning
confidence: 97%